A 12 GHz 30 mW 130 nm CMOS Rotary Travelling Wave Voltage Controlled Oscillator. (14th November 2012) - Jacquemod, G.; Ben Abdeljelil, F.; Carpineto, L.; Tatinian, W.; Borgarino, M.
Abstract : This paper reports a 12 GHz rotary travelling wave (RTW) voltage controlled oscillator designed in a 130 nm CMOS technology. The phase noise and power consumption performances were compared with the literature and with telecommunication standards for broadcast satellite applications. The RTW VCO exhibits a −106 dBc/Hz at 1 MHz and a 30 mW power consumption with a sensibility of 400 MHz/V. Finally, requirements are given for a PLL implementation of the RTW VCO and simulated results are presented.